2017
DOI: 10.1186/s12875-017-0694-1
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for improving practice performance in adult immunizations: a meta-narrative review of the literature

Abstract: BackgroundWe sought to characterize how the term “missed opportunities” is reported in the literature in the context of immunization rates and to assess how missed opportunities can be operationalized.MethodsPeer-reviewed literature searches were conducted in April – May, 2015, to answer: “What methods research studies used to operationalize missed opportunities to vaccinate?” A meta-narrative review methodology was used.ResultsSeven studies met inclusion criteria. The methodologies for quantifying missed oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, missed opportunities for immunization persist. A missed opportunity is any visit to a healthcare provider where a vaccine could have been provided but was not [ 15 ]. One study estimated that eliminating missed opportunities for adults could improve influenza vaccine coverage up to 23% nationally [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, missed opportunities for immunization persist. A missed opportunity is any visit to a healthcare provider where a vaccine could have been provided but was not [ 15 ]. One study estimated that eliminating missed opportunities for adults could improve influenza vaccine coverage up to 23% nationally [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the distinctive elements of our intervention was a deliberate strategy of engaging frontline nursing staff (medical assistants, LPN/RNs) -who are not only responsible for administering vaccines, but through the emergence of team-based clinic workflows, are increasingly empowered to "tee up" health maintenance activities like vaccination on behalf of providers. This, in conjunction with tactics like standing orders, can reduce the likelihood of repeated "missed opportunities" [21,22]. This strategy appears to have succeeded, and was reflected in the dramatic increase, post-intervention, in clinics reporting that non-providers were initiating vaccine conversations with patients and/or reminding providers when the next patient to be seen was due for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…We established baseline immunization rates via EHR data pulls by reviewing immunization performance data for patients seen in the year or influenza season prior to the beginning of the intervention. The definitions for missed opportunities were based on operational methodologies developed by the project team and included population-based, patient/visit-based, and reminder-based approaches [5].…”
Section: Data Collection and Evaluation Data Sourcesmentioning
confidence: 99%
“…We recently explored the missed opportunities in adult vaccinations in a meta-narrative literature review and concluded that missed opportunities are present in various health care settings [5]. Moreover, we reported two methodologies for quantifying missed opportunities: 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation